Household Coping in war- and peacetime: cattle sales in Rwanda, 1991-2001 - Marijke Verpoorten (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2007)
The economic literature has given due attention to household coping strategies in peacetime. In contrast, little is known about such strategies in wartime. This paper studies the use of cattle as a buffer stock by Rwandan households during 1991-2001, a period characterized by civil war and genocide. It is found that the probability of selling cattle increases upon the occurrence of both peacetime and wartime covariant adverse income shocks. The peacetime cattle sales are largely explained by shifts in the household asset portfolio. In contrast, in 1994, the year of the genocide, almost half of the cattle sales were motivated by the need to buy food. However, we argue that the effectiveness of this coping strategy was severely reduced due to the wartime conditions. First, during the year of ethnic violence, cattle prices plummeted to less than half of their pre-genocide value. Second, we find that households most targeted in the violence did not sell cattle. We discuss several explanations for this latter finding.
Keywords: D12; D91; O12; 330; Coping Strategies; Buffer Stock Model; Cattle; Violent Conflict; Rwanda; Buffer Stock; Rind; Politische Unruhen; Haushaltsökonomik; Schätzung; Ruanda